An overview of direct carbon fuel cells and their promising potential on coupling with solar thermochemical carbon production. (July 2022) - Ozalp, N.; Abedini, H.; Abuseada, M.; Davis, R.; Rutten, J.; Verschoren, J.; Ophoff, C.; Moens, D.
Abstract: Fuel cells convert the chemical energy of fuels directly into electricity. They are not limited by the Carnot efficiency granting theoretical efficiency of up to 100% as per Gibbs free energy and enthalpy of formation ratio. Direct carbon fuel cells (DCFCs) electrochemically convert the chemical energy of solid carbon-rich fuels directly into electricity with efficiencies approaching 90%. Once coupled with a high-grade solid carbon-producing solar methane cracking reactor, DCFCs would essentially produce a pure CO2 flue stream that is nearly capture-ready. Unlike most fuel cell types that employ gaseous fuels, DCFCs can utilize high-grade carbon derived from solar methane cracking reactors, allowing for nearly complete fuel utilization with the entropy change. Thus the reversible heat of the cell reaction is practically zero eliminating the need for cooling and heating in steady-state operation. Therefore, they have the potential to leapfrog the technical evolution process towards achieving clean power generation with dramatically higher efﬁciencies and lower emissions by producing a nearly pure CO2 ﬂue stream that is practically capture-ready. However, despite their advantages, DCFCs experience a complication with respect to solid carbon fuel impurities and ash content of the feedstock. This paper provides a concise overview of recent advances in DCFC technology and elaborates on the potential of high-grade carbon produced from solar methane cracking for use as a fuel in DCFCs. The paper demonstrates a promising system coupling DCFCs with solar methane cracking reactors and lays out the challenges of the proposed system, including carbon agglomeration, deposition, and solar reactor clogging problems. Highlights: Review of recent advances in DCFCs. Discussion of the potential of solar thermally produced carbon for use in DCFCs. Review of the production of carbon black via solar methane cracking. A new cleaning mechanism to reduce carbon deposition and clogging. A novel hybrid DCFC-solar methane cracking system for clean power generation.